IMPLEMENTATION OF SMK 3 IN IMPROVING WORK SAFETY ON ROAD INFRASTRUCTURE PROJECTS - Mohamad Machfudin Amirulloh; Sunarko; Dimas Aji Purnomo (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The construction industry experiences high levels of work accidents in road infrastructure projects. Work accidents have a negative impact on worker safety and project productivity. An Occupational Safety and Health Management System (SMK3) is needed to create a safe and healthy work environment. This study aims to analyze the implementation of SMK3 in improving work safety in road projects. This study uses a qualitative approach based on a literature review of academic sources published between 2023 and 2025. This study identifies five important elements in SMK3, namely safety training, procedural compliance, management support, safety culture, and system evaluation. This study found that safety training increases risk awareness and compliance with work procedures. A consistent evaluation system strengthens the system's adaptation to changing project conditions. This study also shows that project management plays an important role in creating a conducive work climate. Two-way communication between workers and management improves understanding of risks in the field. Safety technology has been shown to support real-time hazard detection and accelerate preventive actions. Worker participation in the preparation of safety policies encourages a sense of ownership of a safe work system. This study concludes that a holistic approach strengthens the success of SMK3 implementation in road projects. This study recommends the integration of SMK3 from the planning stage to project implementation. Companies must build an adaptive, collaborative, and risk-based safety management system. The government needs to strengthen safety regulations and improve supervision in the field systematically.